IDENTIFIKASI SISTEM LOGISTIK KOMODITI PERKEBUNAN DI KABUPATEN KEPULAUAN SANGIHE - Lisa V. Mochtar; Caroline B.D. Pakasi; Celsius Talumingan; Paulus A. Pangemanan (Universitas Sam Ratulangi, 2015)
ABSTRACTThis study aims to identify the coconut plantation commodity logistics system in Sangihe Islands District. The method used in this study is a survey method. The data used in this study are primary data and secondary data. Primary data were obtained using the technique of direct interview to farmers and businesses as respondents, using a list of questions (questionnaire) as a tool in data collection. Secondary data were obtained from the department / agencies in the Sangihe Islands District Office of Industry and Trade, Department of Plantations, BAPPEDA, Central Bureau of Statistics and the Department of Transportation. The location of the sample data retrieval, the District of North Tabukan for coconuts and cloves and nutmeg Kendahe for commodities. The determination of these two sub-district based on this location as commodity-producing areas of coconut, nutmeg and cloves highest in Sangihe Islands District as well as most of the villagers are farmers coconut, nutmeg and cloves, so that the two districts are considered to represent the research on logistics system plantation in District Sangihe. Analysis of the data used in this study is a qualitative descriptive analysis where the data obtained will be described to obtain an overview of the process of agricultural commodity logistics and qualitatively analyze the meaning behind the information obtained so composed a systematic knowledge of the process, the reality, of the phenomenon of commodity logistics system plantation in Sangihe Islands District. Furthermore, the data will be analyzed using analysis of network models to determine the shortest route is the path / shortest route in a network. The results showed that the Coconuts are processed into copra farmers then sold to traders, usually through storage by traders to achieve copra delivery quota to a large warehouse. The conclusion of this study is coconut plantation commodity logistics system in the District of Sangihe through three stages ranging from farmers, traders up in the warehouse for distribution to the various regions, where already existing lines patterned in accordance with the timely distribution to Bitung even some which is distributed to the Philippines. Specifically for the commodity nutmeg an cloves, distribution using passenger ship The suggestion in this research is the need for calculation of efficiency and effectiveness analysis of the logistics system of agricultural commodity in Sangihe Islands District to Bitung and the Philippines.Keywords: Logistics, Plantation, Coconut